Angiogenesis is promoted by hypoxic cervical carcinoma-derived extracellular vesicles depending on the endothelial cell environment (2024)
ABSTRACT: Introduction: Cancer needs perfusion for its growth and metastasis. Cancer cell-derived extracellular vesicles (CA-EVs) alter the tumor microenvironment (TME), potentially promoting angiogenesis. We hypothesize that conditions in the tumor, e.g., hypoxia, and in the target cells of the TME, e.g., nutrient deprivation or extracellular matrix, can affect the angiogenic potential of CA-EVs, which would contribute to explaining the regulation of tumor vascularization and its influence on cancer growth and metastasis. Methods: CA-EVs were isolated and characterized from cervical carcinoma cell lines HeLa and SiHa cultured under normoxia and hypoxia, and their angiogenic potential was evaluated in vitro in three endothelial cells (ECs) lines and aortic rings, cultured in basal (growth factor-reduced) or complete medium. Results: Hypoxia increased EV production 10-100 times and protein content 2-4 times compared to normoxic CA-EVs. HeLa-EVs contained six times more RNA than SiHa-EVs, and this concentration was not affected by hypoxia. Treatment with CA-EVs increased tube formation and sprouting in ECs and aortic rings cultured in basal medium and long-term stabilized the stablished vascular networks formed by ECs cultured in complete medium. Conclusion: Hypoxia differentially affects CA-EVs in a cell line-dependent manner. The cellular environment (nutrient availability and extracellular matrix scaffold) influences the effect of CA-EV on the angiogenic potential of ECs. Keywords: Angiogenesis; Cell communication; Extracellular matrix; Extracellular vesicles; Vascular remodeling.